Green synthesis of silver nanoparticles using Trema Orientalis (L.) extract and evaluation of their antibacterial activity - Das R.; Kumar P.; Singh A.K.; Agrawal S.; Albukhaty S.; Bhattacharya I.; Tiwari K.N.; Mishra S.K.; Tripathi A.K.; AlMalki F.A.; Alzubaidi A.K.; Al-Kaabi W.J.; Rajput V.D.; Al-aqbi Z.T. (My University, 2025)
A novel green method was developed to create pure, safe, and stable silver nanoparticles (AgNPs) using Trema orientalis (L.) leaf extract as a reducing and stabilizing agent and evaluated its antibacterial activity. UV-vis spectroscopy indicated the biogenesis of AgNPs based on the absorbance in the range of 400–500 nm. The Fourier transform infrared spectroscopy (FTIR) revealed that flavonoids play a crucial role in the synthesis and stability of green AgNPs, serving as the primary phytoconstituents involved. AgNPs were spherical, and crystalline in nature. The size ranged from 14.04–34.38 nm as determined by transmission electron microscopy (TEM). For phase determination of the crystalline structure, AgNPs were subjected to X-ray diffraction (XRD). The crystallinity percentage calculated was 79.28%. The investigation using atomic force microscopy (AFM) measured the average roughness, maximum height, and valley depth of AgNPs. The mean surface roughness measured was 12.054 nm. The well diffusion method demonstrated the antibacterial activity of AgNPs against Staphylococcus aureus, resulting in inhibition zones measuring 9, 10, 13, and 14 mm. These effects were observed at concentrations of 25 µg/mL, 50 µg/mL, 75 µg/mL, and 100 µg/mL, respectively. The minimum inhibitory concentration observed against S. aureus was 55.31 μg/ml. This work provides a more sustainable and efficient method of bacterial treatment. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.